CRIP UTOPIA AND THE FUTURE OF DISABILITY - Mackey, Peter Joseph (Critical Disability Discourses, 2009)
Thomas More’s seminal work Utopia, written in 1516, has inspired works such as Robert Owen’s A New View of Society (1970) and H.G. Wells’ A Modern Utopia (2005), which theorize their own vision of a perfect society based on socialist ideals of co-operation, interdependence, unity, and harmony. Drawing on cultural Marxist Frederic Jameson’s (2001a; 2001b) critique of the Utopian genre, the author analyzes the two Utopias of Disability Studies scholars Vic Finkelstein (1975; 1980) and Adolf Ratzka (1998), as well as the Anti-Utopian responses of critics Paul Abberley (1996; 1997, 2002) and Tom Shakespeare (2002; 2006). While Utopians Finkelstein and Ratzka work toward dispelling what Jameson refers to as the “collective fantasy” of nondisabled people—that disability is preventable and antithetical to “the good life”—anti-Utopians Abberley and Shakespeare concentrate on the difficulties of the fluidity of the disability/impairment distinction central to Finkelstein’s emphasis on employment.